2006
DOI: 10.1103/physrevb.73.075109
|View full text |Cite
|
Sign up to set email alerts
|

Persistent current and Drude weight in mesoscopic rings

Abstract: We study the persistent current and the Drude weight of a system of spinless fermions, with repulsive interactions and a hopping impurity, on a mesoscopic ring pierced by a magnetic flux, using a Density Matrix Renormalization Group algorithm for complex fields. Both the Luttinger Liquid (LL) and the Charge Density Wave (CDW) phases of the system are considered. Under a Jordan-Wigner transformation, the system is equivalent to a spin-1/2 XXZ chain with a weakened exchange coupling. We find that the persistent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…It is well known that j is strongly size dependent, since it originates from electron coherence across the entire ring [30]. For a perfect metal one expect j to scale as 1/L [25].…”
Section: Scaling Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that j is strongly size dependent, since it originates from electron coherence across the entire ring [30]. For a perfect metal one expect j to scale as 1/L [25].…”
Section: Scaling Propertiesmentioning
confidence: 99%
“…A similar approach has been earlier used to study the effect of disorder on persistent current for the Hubbard model at half-filling [70]. Recently a density matrix renormalization group algorithm has been developed to deal with complex Hamiltonian matrices and used to calculate D c for spinless fermions [30].…”
Section: Homogeneous Rings: General Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Its statistical properties have been much studied in chaotic quantum systems and random matrices [6][7][8][9][10] and in Anderson Localization models [11][12][13][14][15][16][17]. The case of the ground state energy in interacting quantum models has been analyzed both without disorder [18,19] and with disorder [20][21][22], in particular to characterize the persistent currents induced by a magnetic flux in mesoscopic rings. The case of highly excited eigenstates in a disordered model of interactions fermions has been investigated very recently [23] in the context of the Many-Body-Localization problem (see the recent reviews [24,25] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…It is thus important, both on the experimental and fundamental level, to understand and develop physical intuition concerning the effects of strong correlations on the Drude weight. It is commonly believed that repulsive interactions reduce particle mobility in a many-body system, leading to a generic reduction of the Drude weight [15,[35][36][37]. Nevertheless, it was recently observed that this fact is remarkably violated in Creutz ladders [38]: this was attributed to the presence of an isolated Dirac cone and put into relation to the anomalous magnetic orbital response of 2D graphene [39].…”
Section: Introductionmentioning
confidence: 99%